Spazio e percezione nella ricerca di Massimo Bartolini (Itinera, 2013)
This paper aims at providing a thorough examination of one possible interpretations of the relationship between art and senses within the field of contemporary visual arts, through a specifically identified case study: Massimo Bartolini’s works. In particular, a selected number of works based on synaesthesia has been chosen (Casa di Francesca Sorace, 1993; Mixing Parfums, 2000; El Jardì de Roses, la Font de Pedres, 2007; La strada di sotto, 2011): these projects concern environmental distortion aiming to redefine the perception of space questioning the usual and established modalities of fruition.